Um olhar sobre a verdade: a força do dizer verdadeiro nos depoimentos de ex-estudantes publicados no volume 9 do Relatório final da Comissão da verdade da Universidade de São Paulo (CV-USP) - Leite, Arthur Damasceno Ribeiro de Oliveira (2023)
The present thesis aims to problematize the relationship between one individual with the truth in the final report of the Truth Commission of the University of São Paulo (CV-USP) and was developed within the scope of the Research Line History and Historiography of Education, Graduate Program in Education at the Faculty of Education of the Universidade Federal de Uberlândia. Through a methodological approach, focused on the testimonies of former students published in Volume 9 of the CV-USP, we aspire to investigate how truth was produced in the speech of these witnesses, how it manifests through the statements of truth that these subjects uphold, and, in this context, we wanted to understand the form of the subject who speaks the truth in the report. In order to answer these questions, we conducted documentary research in the final reports of the National Truth Commission (CNV) and CV-USP, an exploratory bibliographic study in the BDTD and in the Capes Periodicals Portal, as well as a theoretical philosophical investigation by engaging with the work and thought of Michel Foucault. This includes addressing specific categories such as: subject, truth, subjectivity, aleturgy, self aleturgy, parrhesia, courage of truth, truthful-speaking, ethos, and existential cynicism traditionalism. As a result, we argue that the truth games proposed by CV-USP stimulated the witnesses to produce a truthful-speaking as self-aleturgy, in the first person of enunciation, a truth that, when manifested in the speech of former students through a specific modality of veridiction – imprecatory parrhesia – points to the Parrhesia Game and to the ethos of the parrhesiast; to the form of the subject who, by speaking the truth, manifests their courage. Therefore, we propose that the testimonies of former students, victims of serious human rights violations committed by the civil-military dictatorship (1964-1985) at USP, reveal subjectivities that, relying on the courage of their truthful-speaking, denounce crimes, question the State about past violence against the population, and, above all, through this exercise of freedom, express an ethos forged in the parrhesiastic pact of the subject with the truth they uphold, revealing a subjective position of resistance against forgetting, which also refers to traces of an existential cynicism traditionalism: sometimes of the Philosophical Hero, sometimes of the Revolutionary. Above all, it indicates the ethos of the one who exhorts self-care as the first step towards the care of all humanity, expressing the function of katáskopos: the one who went to the forefront of humanity and returned to indicate the dangers. Thus, in our study, we attempt to show how the testifying subjects use the parrhesia game to educate: to remember in order to not repeat it